Ships and Relation-Ships: Tie Formation in the Sector of Service Intermediaries in Shipping - Agnieszka Nowińska (Copenhagen Business School (CBS), 2018)
The aim of the dissertation is to shed light on the complex determinants of tie formation. Extant research has linked similarity and dissimilarity (respectively homophily and heterophily) and different proximities types to the likelihood of tie formation in a linear way. However, there are significant differences in how ties form depending on 1) tie characteristics (formal vs informal), 2) group belonging (female vs. male), 3) types of proximities involved and their interplay, 4) temporal dynamics. Therefore, to fill gaps in the literature, this dissertation addresses the question on how the likelihood of tie formation is correlated with 1) the interplay of geographical and industry space proximities in formal inter-firm ties over time, 2) organizational and geographical proximity in case of formal employer-employee ties after organizational failure 3) gender homophily for females and males in case of informal employee-employee ties. I use the empirical setting of service intermediaries: shipbrokers and bunker traders, in the international shipping industry. My methodological approach includes mixed (qualitative and quantitative) methods and a quasi-natural experiment. The dissertation comprises three empirical studies that address the research questions outlined. The dissertation's main contribution lies in demonstrating the complexity of tie determinants. The first chapter explains the premises, gap, empirical setting, methods and contribution of this dissertation. The following chapter (Chapter 2) analyses the role and interplay of geographical proximity and buyers' types (such as competitors) for the tie formation in formal inter-firm transactions in shipbroking. I find that the effect of geographical proximity does not significantly correlate with tie formation between the focal shipbroker firm and the buyers, it however positively moderates the lower likelihood of dealing with competitors. This finding is explained with co-opetition (simultaneous pursuit of cooperation and competition) in local clusters of service firms. Chapter 3 studies the unexpected and exogenous organizational failure following a fraud and its effects on the status change of displaced employees transitioning into new employment. While there is no generalized stigma in the studied setting, employees organizationally and geographically proximate to the pivot of the failure are more prone to a status loss in guise of lower level jobs or jobs at lower status firms. The mechanisms that explains such a systematic pattern of status loss is blame. Similar to stigma by its spillover effects, it operates however less spread therefore, in contrast to stigma's “wide brush”, the blame taints with a “pointed brush”. Further, Chapter 4 analyses the differential effects of gender homophily for females and males on the likelihood of co-mobility: while male dyads are more likely to be co-mobile, female dyads are less likely to be co-mobile. By further investigating possible underlying mechanisms, the chapter finds a strong support for labor market discrimination driving the results for female dyads.
hdl:10398/9655
Keywords: 650